(untitled) (SCIENCE TIME JOURNAL, 2026)
This study investigates the role of cognitive strategies in foreign language vocabulary acquisition at the university level. Grounded in cognitive learning theory and the depth of processing framework, the research examines how different cognitive strategies - such as repetition, contextual usage, inferencing, imagery, and semantic mapping - affect students’ vocabulary learning outcomes. A mixed-method research design was employed, combining quantitative and qualitative approaches to ensure comprehensive analysis and data triangulation. The participants were 65 first-year university students with similar English proficiency levels. Data were collected through a vocabulary learning strategies questionnaire, a vocabulary knowledge test, and semi-structured interviews. Quantitative findings revealed a significant positive correlation between the frequency of cognitive strategy use and vocabulary achievement. Qualitative analysis further indicated that high-achieving students employed a wider range of elaborative strategies, while low-achieving students relied mainly on mechanical repetition and translation. The findings highlight the necessity of explicit instruction in cognitive vocabulary learning strategies and suggest integrating systematic strategy training into university-level EFL and ESP curricula to enhance vocabulary retention and learner autonomy.